Teaching english for agriculture through proverbs in l1 and l2 - Carreira, Vivina Almeida (2017)
This paper addresses the role of translation and mother tongue as fruitful teaching and learning resources in the case of English for Specific Purposes, particularly the study and translation of proverbs in the process of teaching and learning English for agriculture. It results from a research work involving classroom activities with the translation of proverbs, understood as tradition handed down from generation to generation, as a way of identifying, in different manners of expression, deep roots of cultural influence, as well as to perceive undercurrents of ideas – ethical, political, aesthetic, literary, scientific, etc. – in the history of peoples’ cultures. Agriculture is a rich field of proverbial heritage in most cultures and so proverbs can most productively be used to various purposes within the English class. From conveying the difference between linguistic and cultural competence, linguistic and idiomatic meaning, literal and figurative language, written and spoken language to vocabulary acquisition and retention, proverbs can unfold in a multitude of classroom activities demonstrating their huge application potential and didactic power.